نفحات التنقیح فی شرح مشكاة المصابیح كے اسلوب و منہج كا جائزہ: A review of the style and method of Nafhat al-Tanqih on Sharh Mishkaat al-Masabih - Dr.MuhammadAhmad Zuberi (MEI, 2024)
The research paper titled "A Review of the Style and Methodology of Nafhat al-Tanqeeh" explores the distinctive approach and methodology used in this detailed commentary on Mishkat al-Masabih, a prominent Hadith collection, by Maulana Salimullah Khan. The paper begins by highlighting the historical significance of Mishkat al-Masabih, which has been a part of the curriculum for centuries in the subcontinent, serving as a comprehensive compilation of the teachings and sayings of Prophet Muhammad (PBUH). Maulana Salimullah Khan's commentary, Nafhat al-Tanqeeh, is rooted in his lifelong engagement with teaching Mishkat. The work is organized into six volumes, providing an in-depth exegesis of the Hadiths with a special focus on the linguistic, jurisprudential, and theological aspects. The commentary is known for its structured explanation of difficult topics, making them accessible to students and scholars alike. The research further delves into Khan's teaching style, which simplifies complex scholarly debates while maintaining accuracy. His ability to address conflicting views among various Islamic schools of thought, and his integration of Quranic evidence to support his explanations, are major highlights of his work. Additionally, the paper underscores the impact of Nafhat al-Tanqeeh on Islamic scholarship, emphasizing how it serves as a reference for both teachers and students in Hadith sciences. Key words: Hadith Collections ,Mishkat,Subcontinent,Sayings of HolyProphet.